Click chemistry extracellular vesicle/peptide/chemokine nanocarriers for treating central nervous system injuries - Huitong Ruan; Yongfang Li; Cheng Wang; Yixu Jiang; Yulong Han; Yiwei Li; Dandan Zheng; Jing Ye; Gang Chen; Guo-yuan Yang; Lianfu Deng; Ming Guo; et al. (Elsevier, 2023)
Central nervous system (CNS) injuries, including stroke, traumatic brain injury, and spinal cord injury, are essential causes of death and long-term disability and are difficult to cure, mainly due to the limited neuron regeneration and the glial scar formation. Herein, we apply extracellular vesicles (EVs) secreted by M2 microglia to improve the differentiation of neural stem cells (NSCs) at the injured site, and simultaneously modify them with the injured vascular targeting peptide (DA7R) and the stem cell recruiting factor (SDF-1) on their surface via copper-free click chemistry to recruit NSCs, inducing their neuronal differentiation, and serving as the nanocarriers at the injured site (Dual-EV). Results prove that the Dual-EV could target human umbilical vascular endothelial cells (HUVECs), recruit NSCs, and promote the neuronal differentiation of NSCs in vitro. Furthermore, 10 miRNAs are found to be upregulated in Dual-M2-EVs compared to Dual-M0-EVs via bioinformatic analysis, and further NSC differentiation experiment by flow cytometry reveals that among these miRNAs, miR30b-3p, miR-222-3p, miR-129-5p, and miR-155-5p may exert effect of inducing NSC to differentiate into neurons. In vivo experiments show that Dual-EV nanocarriers achieve improved accumulation in the ischemic area of stroke model mice, potentiate NSCs recruitment, and increase neurogenesis. This work provides new insights for the treatment of neuronal regeneration after CNS injuries as well as endogenous stem cells, and the click chemistry EV/peptide/chemokine and related nanocarriers for improving human health.